Ernesto Buonaiuti. Tra liberalismo modernista e socialismo cristiano - Zarlenga, Achille (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The aim of this paper is to explore the connection between heresy and liberalism. Its purpose is to show an alternative approach by putting liberal political doctrine in contact with a heterodox religious theory, which is modernism. This movement, struck by official Papal excommunication, is apparently linked to the liberalism and is connected to the socialist theory of the French philosopher Georges Sorel. This results clear by looking at the early works of Roman priest Ernesto Buonaiuti, one of the most persecuted modernist by the Vatican. Many of Buonaiuti’s papers and books, which were published in the first decade of the 20th century , show such a great interest for the socialist doctrines to the point that it is almost possible to talk of a “Christian socialism”. However, modernism and many modernists were oppressed by the ecclesiastical institution and secular intellectuals, condemning one of the most important Italian’s sociocultural movement to a forgetfulness that still stands.